2020
DOI: 10.1021/acssuschemeng.0c02290
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Functionalized Aromatic Carboxylic Acids from Biosourced 3-Hydroxy-2-pyrones through a Base-Promoted Domino Reaction

Abstract: Nowadays, the use of biomass derived synthons as precursors of aromatic products is an important research topic in green chemistry. In particular, the Diels−Alder protocol has been applied in the construction of valuable aromatic derivatives such as terephthalic acid and esters using muconic acid and 2-pyrones as diene components. In this context, we now propose the use of 3hydroxy-2-pyrones, prepared from galactaric acid, as building block for the synthesis of functionalized aromatic carboxylic acids. Our pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Ring substituents play a critical role in the cycloadditions of 2( H )pyran-2-ones. Generally speaking, the unsubstituted ring 2( H )pyran-2-one, 18 ( Figure 2 ), undergoes cycloadditions only under harsh conditions and with alkynes to afford benzenes following the tandem loss of CO 2 [ 1 , 2 , 3 , 4 , 5 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Examples of cycloadditions of 2( H )pyran-2-one, 18, with alkenes to afford bridged bicyclic lactones do exist, but are rare [ 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ring substituents play a critical role in the cycloadditions of 2( H )pyran-2-ones. Generally speaking, the unsubstituted ring 2( H )pyran-2-one, 18 ( Figure 2 ), undergoes cycloadditions only under harsh conditions and with alkynes to afford benzenes following the tandem loss of CO 2 [ 1 , 2 , 3 , 4 , 5 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Examples of cycloadditions of 2( H )pyran-2-one, 18, with alkenes to afford bridged bicyclic lactones do exist, but are rare [ 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, cycloadditions of 2( H )pyran-2-one dienes to alkene dienophiles affords bridged bicyclic lactones, e.g., 2 which can then be transformed in few steps to highly substituted, six-membered rings, e.g., 3 ( Scheme 1 ) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Under more forcing conditions, typically at higher temperatures, cycloadditions to alkyne dienophiles and subsequent aromatization via loss of bridging CO 2 leads to substituted benzenes, e.g., 4 [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, cycloadditions with alkenes 227 yield isolable adducts 228, representing useful synthetic intermediates due to their structural and stereochemical inimitability. [85][86][87] Since Diels and Alder published in 1931 that 2-pyrones could function as a diene component in [4 + 2]cycloadditions, [88] this strategy has emerged as a powerful tool for the synthesis of aromatics, heteroaromatics and natural products. [85][86][87] Especially, the ability to form aromatic products from pyrones has been widely exploited.…”
Section: [4 + 2]-cycloadditionmentioning
confidence: 99%
“…[85][86][87] Since Diels and Alder published in 1931 that 2-pyrones could function as a diene component in [4 + 2]cycloadditions, [88] this strategy has emerged as a powerful tool for the synthesis of aromatics, heteroaromatics and natural products. [85][86][87] Especially, the ability to form aromatic products from pyrones has been widely exploited. For instance, Garg et al demonstrated, that an additional benzene ring can be easily introduced to oxygen-or nitrogen-containing strained alkynes 230 (Scheme 45).…”
Section: [4 + 2]-cycloadditionmentioning
confidence: 99%
See 1 more Smart Citation